Sintomas comuns de depressão e estresse percebido em estudantes universitários da área da saúde - Bresolin, Julia Zancan (2018)
The psychological characteristics of a student must be considered since its admission in the academic environment because many modifications, challenges and responsibilities are present in this period. Due to this occurrence, stress and depression can manifest as an adversity. This study main goal was to evaluate the association between common symptoms of depression and perceived stress in health care undergraduate students. It’s a cross-sectional study developed with health care undergraduates in a public university in Rio Grande do Sul. Probabilistic sample with clusters was used. The research instrument was a questionnaire that could identify variables of social demographic, health and academic habits. Beck Depression Inventory-II was used to measure the common depression symptoms and to evaluate the students’ stress level the Brazilian version of the Perceived Stress Scale was applied. For the analysis it was utilized descriptive statistics with frequency distribution and position and dispersion measurements; bivariate analysis with chi-square test as well as comparison of the means; multivariate analysis through Poisson’s regression; and Pearson’s correlation. The study’s final sample consisted in 792 students. Depression appeared between moderate and severe in 23,6% of the health care undergraduates. The major with the biggest prevalence of the depression was Speech Therapy followed by Nursing. The highest prevalence of moderate to severe common depression symptoms was in female obese students, that use the bus as means of transportation, that don’t exercise nor have time for leisure activities. The means of perceived stress was 30,22 (±8,47). High levels of stress was presented in 9,5 of the students and the highest prevalence was in Speech Therapy and Medicine majors. It was displayed that the higher the depression level, the higher the perceived stress means. It was observed a significant statistical difference between perceived stress and depression among the Speech Therapy, Nursing, Pharmacy, Medicine, Occupational Therapy and Physical Therapy. The data analysis showed a high prevalence of depression and stress in undergraduates and that there is an association amid the investigated phenomena. It is advised to administrators, professors and to the Health Science headquarter to develop strategies to prevent students from having some kind of psychological illness.